Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Collective and harmonized high throughput barcoding of insular arthropod biodiversity: Toward a Genomic Observatories Network for islands - Brent C. Emerson; Paulo A. V. Borges; Pedro Cardoso; Peter Convey; Jeremy R. deWaard; Evan P. Economo; Rosemary G. Gillespie; Susan Kennedy; Henrik Krehenwinkel; Rudolf Meier; George K. Roderick; Dominique Strasberg; et al. (Molecular Ecology, 2023)
Current understanding of ecological and evolutionary processes underlying island biodiversity is heavily shaped by empirical data from plants and birds, although arthropods comprise the overwhelming majority of known animal species, and as such can provide key insights into processes governing biodiversity. Novel high throughput sequencing (HTS) approaches are now emerging as powerful tools to overcome limitations in the availability of arthropod biodiversity data, and hence provide insights into these processes. Here, we explored how these tools might be most effectively exploited for comprehensive and comparable inventory and monitoring of insular arthropod biodiversity. We first reviewed the strengths, limitations and potential synergies among existing approaches of high throughput barcode sequencing. We considered how this could be complemented with deep learning approaches applied to image analysis to study arthropod biodiversity. We then explored how these approaches could be implemented within the framework of an island Genomic Observatories Network (iGON) for the advancement of fundamental and applied understanding of island biodiversity. To this end, we identified seven island biology themes at the interface of ecology, evolution and conservation biology, within which collective and harmonized efforts in HTS arthropod inventory could yield significant advances in island biodiversity research.

Richness and resilience in the Pacific: DNA metabarcoding enables parallelized evaluation of biogeographic patterns - Susan Kennedy; Jerilyn Calaor; Yazmín Zurápiti; Julian Hans; Masashi Yoshimura; Juanita Choo; Jeremy C. Andersen; Jackson Callaghan; George K. Roderick; Henrik Krehenwinkel; Haldre Rogers; Rosemary G. Gillespie; et al. (Molecular Ecology, 2023)
Islands make up a large proportion of Earth's biodiversity, yet are also some of the most sensitive systems to environmental perturbation. Biogeographic theory predicts that geologic age, area, and isolation typically drive islands' diversity patterns, and thus potentially impact non‐native spread and community homogenization across island systems. One limitation in testing such predictions has been the difficulty of performing comprehensive inventories of island biotas and distinguishing native from introduced taxa. Here, we use DNA metabarcoding and statistical modelling as a high throughput method to survey community‐wide arthropod richness, the proportion of native and non‐native species, and the incursion of non‐natives into primary habitats on three archipelagos in the Pacific – the Ryukyus, the Marianas and Hawaii – which vary in age, isolation and area. Diversity patterns largely match expectations based on island biogeography theory, with the oldest and most geographically connected archipelago, the Ryukyus, showing the highest taxonomic richness and lowest proportion of introduced species. Moreover, we find evidence that forest habitats are more resilient to incursions of non‐natives in the Ryukyus than in the less taxonomically rich archipelagos. Surprisingly, we do not find evidence for biotic homogenization across these three archipelagos: the assemblage of non‐native species on each island is highly distinct. Our study demonstrates the potential of DNA metabarcoding to facilitate rapid estimation of biogeographic patterns, the spread of non‐native species, and the resilience of ecosystems.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Towards a genetic theory of island biogeography: Inferring processes from multidimensional community‐scale data - Isaac Overcast; Guillaume Achaz; Robin Aguilée; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Evan P. Economo; Rampal S. Etienne; Rosemary Gillespie; Claire Jacquet; Flora Jay; Susan Kennedy; et al. (Global Ecology and Biogeography, 2023)
Background MacArthur and Wilson's theory of island biogeography has been a foundation for obtaining testable predictions from models of community assembly and for developing models that integrate across scales and disciplines. Historically, however, these developments have focused on integration across ecological and macroevolutionary scales and on predicting patterns of species richness, abundance distributions, trait data and/or phylogenies. The distribution of genetic variation across species within a community is an emerging pattern that contains signatures of past population histories, which might provide an historical lens for the study of contemporary communities. As intraspecific genetic diversity data become increasingly available at the scale of entire communities, there is an opportunity to integrate microevolutionary processes into our models, moving towards development of a genetic theory of island biogeography. Motivation/goal We aim to promote the development of process‐based biodiversity models that predict community genetic diversity patterns together with other community‐scale patterns. To this end, we review models of ecological, microevolutionary and macroevolutionary processes that are best suited to the creation of unified models, and the patterns that these predict. We then discuss ongoing and potential future efforts to unify models operating at different organizational levels, with the goal of predicting multidimensional community‐scale data including a genetic component. Main conclusions Our review of the literature shows that despite recent efforts, further methodological developments are needed, not only to incorporate the genetic component into existing island biogeography models, but also to unify processes across scales of biological organization. To catalyse these developments, we outline two potential ways forward, adopting either a top‐down or a bottom‐up approach. Finally, we highlight key ecological and evolutionary questions that might be addressed by unified models including a genetic component and establish hypotheses about how processes across scales might impact patterns of community genetic diversity.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Stream flow alone does not predict population structure of diving beetles across complex tropical landscapes - Athena Lam; Emmanuel F. A. Toussaint; Carolin Kindler; Matthew H. Van Dam; Rawati Panjaitan; George K. Roderick; Michael Balke (Molecular Ecology, 2018)
Recent theoretical advances have hypothesized a central role of habitat persistence on population genetic structure and resulting biodiversity patterns of freshwater organisms. Here, we address the hypothesis that lotic species, or lineages adapted to comparably geologically stable running water habitats (streams and their marginal habitats), have high levels of endemicity and phylogeographic structure due to the persistent nature of their habitat. We use a next RAD DNA sequencing approach to investigate the population structure and phylogeography of a putatively widespread New Guinean species of diving beetle, Philaccolilus ameliae (Dytiscidae). We find that P. ameliae is a complex of morphologically cryptic, but geographically and genetically well‐differentiated clades. The pattern of population connectivity is consistent with theoretical predictions associated with stable lotic habitats. However, in two clades, we find a more complex pattern of low population differentiation, revealing dispersal across rugged mountains and watersheds of New Guinea up to 430 km apart. These results, while surprising, were also consistent with the original formulation of the habitat template concept by Southwood, involving lineage‐idiosyncratic evolution in response to abiotic factors. In our system, low population differentiation might reflect a young species in a phase of range expansion utilizing vast available habitat. We suggest that predictions of life history variation resulting from the dichotomy between lotic and lentic organisms require more attention to habitat characterization and microhabitat choice. Our results also underpin the necessity to study fine‐scale processes but at a larger geographical scale, as compared to solely documenting macroecological patterns, to understand ecological drivers of regional biodiversity. Comprehensive sampling especially of tropical lineages in complex and threatened environments such as New Guinea remains a critical challenge.

Phylogeography and population genomics of a lotic water beetle across a complex tropical landscape - Athena Wai Lam; Morgan Gueuning; Carolin Kindler; Matthew Van Dam; Nadir Alvarez; Rawati Panjaitan; Helena Shaverdo; Lloyd T. White; George K. Roderick; Michael Balke (Molecular Ecology, 2018)
The habitat template concept applied to a freshwater system indicates that lotic species, or those which occupy permanent habitats along stream courses, are less dispersive than lentic species, or those that occur in more ephemeral aquatic habitats. Thus, populations of lotic species will be more structured than those of lentic species. Stream courses include both flowing water and small, stagnant microhabitats that can provide refuge when streams are low. Many species occur in these microhabitats but remain poorly studied. Here, we present population genetic data for one such species, the tropical diving beetle Exocelina manokwariensis (Dytiscidae), sampled from six localities along a ~300 km transect across the Birds Head Peninsula of New Guinea. Molecular data from both mitochondrial (CO1 sequences) and nuclear (ddRAD loci) regions document fine‐scale population structure across populations that are ~45 km apart. Our results are concordant with previous phylogenetic and macroecological studies that applied the habitat template concept to aquatic systems. This study also illustrates that these diverse but mostly overlooked microhabitats are promising study systems in freshwater ecology and evolutionary biology. With the advent of next‐generation sequencing, fine‐scale population genomic studies are feasible for small nonmodel organisms to help illuminate the effect of habitat stability on species’ natural history, population structure and geographic distribution.

Stepping‐stones across space and time: repeated radiation of Pacific flightless broad‐nosed weevils (Coleoptera: Curculionidae: Entiminae: Rhyncogonus ) - Elin M. Claridge; Rosemary G. Gillespie; Michael S. Brewer; George K. Roderick (Journal of Biogeography, 2017)
Aim We examine spatial and temporal patterns of diversification among flightless weevils in the genus Rhyncogonus (Curculionidae: Entiminae), with respect to their passive mode of dispersal by rafting or upon birds and the geological context of Pacific island archipelagos. Location Archipelagos and islands of the Pacific Ocean, especially the South Pacific and Hawaii. Methods Nuclear and mitochondrial DNA sequence data were used in Bayesian and maximum likelihood analyses to generate a phylogenetic hypothesis for all available species within the genus Rhyncogonus , plus representatives of other tribes in the subfamily Entiminae. Bayesian inference with molecular and geological calibration points was also used to estimate the age of major lineages of Rhyncogonus and infer the history of colonization. Results The genus Rhyncogonus has colonized all major archipelagos in the central Pacific, with multiple species occurring within nearly all archipelagos. The common ancestors of the genus were present in the central Pacific at least 15 Ma, probably first inhabiting islands now under water. Subsequent colonization and diversification across Oceania shows a pattern that is remarkably consistent with the geology of the region: the weevils, which likely disperse either by rafting on vegetation or on migratory birds, reached each island not long after its appearance. Main conclusions Though flightless, weevils in the genus Rhyncogonus have been remarkably effective at colonizing islands of the Pacific and appear to have colonized more remote islands via a series of less remote archipelagos. Although such a process of dispersal has been predicted, this study provides the first clear demonstration of the role of stepping‐stones in the diversification of a lineage with passive dispersal.

Temporal dynamics influenced by global change: bee community phenology in urban, agricultural, and natural landscapes - Misha Leong; Lauren C. Ponisio; Claire Kremen; Robbin W. Thorp; George K. Roderick (Global Change Biology, 2016)
Urbanization and agricultural intensification of landscapes are important drivers of global change, which in turn have direct impacts on local ecological communities leading to shifts in species distributions and interactions. Here, we illustrate how human‐altered landscapes, with novel ornamental and crop plant communities, result not only in changes to local community diversity of floral‐dependent species, but also in shifts in seasonal abundance of bee pollinators. Three years of data on the spatio‐temporal distributions of 91 bee species show that seasonal patterns of abundance and species richness in human‐altered landscapes varied significantly less compared to natural habitats in which floral resources are relatively scarce in the dry summer months. These findings demonstrate that anthropogenic environmental changes in urban and agricultural systems, here mediated through changes in plant resources and water inputs, can alter the temporal dynamics of pollinators that depend on them. Changes in phenology of interactions can be an important, though frequently overlooked, mechanism of global change.

First report of the Sub-Saharan Africa 2 species of the Bemisia tabaci complex in the Southern France - Margarita Hadjistylli; George K. Roderick; Nathalie Gauthier (Phytoparasitica, 2015)

A range‐wide genetic bottleneck overwhelms contemporary landscape factors and local abundance in shaping genetic patterns of an alpine butterfly (Lepidoptera: Pieridae: Colias behrii ) - SEAN D. SCHOVILLE; ATHENA W. LAM; GEORGE K. RODERICK (Molecular Ecology, 2012)
Spatial and environmental heterogeneity are major factors in structuring species distributions in alpine landscapes. These landscapes have also been affected by glacial advances and retreats, causing alpine taxa to undergo range shifts and demographic changes. These nonequilibrium population dynamics have the potential to obscure the effects of environmental factors on the distribution of genetic variation. Here, we investigate how demographic change and environmental factors influence genetic variation in the alpine butterfly Colias behrii . Data from 14 microsatellite loci provide evidence of bottlenecks in all population samples. We test several alternative models of demography using approximate Bayesian computation (ABC), with the results favouring a model in which a recent bottleneck precedes rapid population growth. Applying independent calibrations to microsatellite loci and a nuclear gene, we estimate that this bottleneck affected both northern and southern populations 531–281 years ago, coinciding with a period of global cooling. Using regression approaches, we attempt to separate the effects of population structure, geographical distance and landscape on patterns of population genetic differentiation. Only 40% of the variation in F ST is explained by these models, with geographical distance and least‐cost distance among meadow patches selected as the best predictors. Various measures of genetic diversity within populations are also decoupled from estimates of local abundance and habitat patch characteristics. Our results demonstrate that demographic change can have a disproportionate influence on genetic diversity in alpine species, contrasting with other studies that suggest landscape features control contemporary demographic processes in high‐elevation environments.

Species Differentiation on a Dynamic Landscape: Shifts in Metapopulation Genetic Structure Using the Chronology of the Hawaiian Archipelago - George K. Roderick; Peter J. P. Croucher; Amy G. Vandergast; Rosemary G. Gillespie (Evolutionary Biology, 2012)

Pleistocene origin and population history of a neoendemic alpine butterfly - SEAN. D. SCHOVILLE; MATTHEW STUCKEY; GEORGE K. RODERICK (Molecular Ecology, 2011)
Alpine environments underwent dramatic transformation during glacial–interglacial cycles, with the consequence that geographical, ecological and demographic changes of alpine populations provided the opportunity for formation of neoendemic species. Several biogeographical models have been proposed to account for the unique history of alpine populations, with different expectations of genetic divergence and speciation. The expanding alpine archipelago model proposes that alpine populations expand spatially and demographically during glacial events, dispersing between mountain ranges. Under this model, alpine populations are unlikely to diverge in isolation due to substantial interpopulation gene flow. In contrast, the alpine archipelago refuge model proposes that gene flow during glacial phases is limited and populations expand demographically during interglacial phases, increasing genetic isolation and the likelihood of speciation. We assess these models by reconstructing the evolutionary history of Colias behrii , a morphologically and ecologically distinct alpine butterfly restricted to the California Sierra Nevada. C. behrii exhibits very low genetic diversity at mitochondrial and nuclear loci, limited population structure and evidence of population expansion. C. behrii and Rocky Mountain C. meadii share identical mitochondrial haplotypes, while in contrast, nuclear data indicate common ancestry between C. behrii and Cascades Range Colias pelidne . The conflict in gene genealogies may be a result of recent expansion in North American Colias, but an isolation with migration analysis indicates that genetic patterns in C. behrii might result from differential introgression following hybridization. Based on the timing of population expansion and gene flow between mountain ranges, the expanding alpine archipelago model is supported in C. behrii .

Recent emergence and worldwide spread of the red tomato spider mite, Tetranychus evansi: genetic variation and multiple cryptic invasions - Angham Boubou; Alain Migeon; George K. Roderick; Maria Navajas (Biological Invasions, 2011)

Post-colonization temporal genetic variation of an introduced fly, Rhagoletis completa - Yolanda H. Chen; Stewart H. Berlocher; Susan B. Opp; George K. Roderick (Genetica, 2010)

Successful spread of a biocontrol agent reveals a biosecurity failure: elucidating long distance invasion pathways for Gonatocerus ashmeadi in French Polynesia - Jérôme N. Petit; Mark S. Hoddle; Julie Grandgirard; George K. Roderick; Neil Davies (BioControl, 2009)

Alpine biogeography of Parnassian butterflies during Quaternary climate cycles in North America - SEAN D. SCHOVILLE; GEORGE K. RODERICK (Molecular Ecology, 2009)
Growth of alpine glaciers during the Pleistocene had profound effects on montane landscapes in North America and the organisms now inhabiting alpine ecosystems. Biogeography of this region has often been viewed as a system of sky islands despite the fact that species richness patterns deviate from a strict island biogeographic model. One explanation is that alpine species are not in equilibrium because of late Quaternary geographic range shifts. Genetic data can provide evidence of nonequilibrium dynamics and the distributional shifts that occur during glaciation events in alpine landscapes. Using mitochondrial and nuclear sequence data, we examine the evolutionary history of butterflies in the Parnassius phoebus complex. We test explicit, alternative models of the biogeographic history of Parnassius smintheus and Parnassius behrii , including an equilibrium island model, ancestral radiation and fragmentation, an expanding alpine archipelago and an alpine archipelago refuge model. Our results support the alpine archipelago refuge model, in which alpine butterflies undergo population contraction during glacial climates followed by population expansion during interglacial phases. While butterflies can disperse between distant mountain ranges during glacial periods, gene flow is rare. We find evidence of recent connectivity between California and Colorado, population expansion events following deglaciation ∼20 000 years B.P., and small population sizes during the last glacial period. An analysis of lineage splitting suggests that morphological differences in P. smintheus and P. behrii are the result of late Pleistocene divergence (∼48 000 years B.P.) with limited gene flow. Our results demonstrate that spatially complex and nonequilibrium population dynamics influence alpine diversity patterns.

Tracing the invasion history of mealy plum aphid, Hyalopterus pruni (Hemiptera: Aphididae), in North America: a population genetics approach - Jeffrey D. Lozier; George K. Roderick; Nicholas J. Mills (Biological Invasions, 2009)

Invasion dynamics of the glassy-winged sharpshooter Homalodisca vitripennis (Germar) (Hemiptera: Cicadellidae) in French Polynesia - Jérôme N. Petit; Mark S. Hoddle; Julie Grandgirard; George K. Roderick; Neil Davies (Biological Invasions, 2008)

Engineering an invasion: classical biological control of the glassy-winged sharpshooter, Homalodisca vitripennis, by the egg parasitoid Gonatocerus ashmeadi in Tahiti and Moorea, French Polynesia - Julie Grandgirard; Mark S. Hoddle; Jerome N. Petit; George K. Roderick; Neil Davies (Biological Invasions, 2008)

Biodiversity dynamics in isolated island communities: interaction between natural and human‐mediated processes - ROSEMARY G. GILLESPIE; ELIN M. CLARIDGE; GEORGE K. RODERICK (Molecular Ecology, 2008)
The flora and fauna of oceanic islands have inspired research since the early scientific explorations. Islands can be considered ‘nature's test tubes’— simple systems with multiple replicates. Our research has used the simplicity of island systems to understand ecological community dynamics and to compare the properties of island communities with those in more complex mainland systems. Here, we present three topics: (i) current patterns of biodiversity on isolated islands of the Pacific; (ii) current patterns of disturbance and invasion on islands; and (iii) future trajectories inferred from these patterns. We examine features of islands (in particular, topography and isolation) that have allowed for given levels and distribution of endemicity. The extent to which island communities are impacted by, resist or accommodate disturbance and/or invasions by nonindigenous species appears to be dictated to a large extent by properties of the native communities and how these communities were originally assembled. Accordingly, patterns of disturbance and invasion are very different for high (montane) islands that are extremely isolated compared to those that are nearer to a source of natural migrants. As with all biotas, those on islands are dynamic entities. However, the unique aspect of islands is their isolation, and extreme isolation has largely been lost over the course of the last few centuries due to the development of transportation routes. We argue that such a modified dynamic will affect the future of the biota and the processes that gave rise to the biota. Specifically for isolated habitats, ecological processes will become increasingly more likely to generate biodiversity than evolutionary processes which have been relatively more important in the past. In the short term, island biotas and other similar biotas that occur in montane habitats may fare well as species are often abundant locally in the habitat to which they are indigenous, and may demonstrate considerable resistance and resilience to invasion. However, island biotas — and other biotas that show high local endemism — will likely not fare well in the face of prolonged disturbance. The biotas in these areas generally display a relatively low dispersal capacity; therefore, under conditions of long‐term habitat modification, isolated biotas are likely to be swamped by non‐natives, which — simply because of random processes and higher propagule pressure — will move more readily into available habitats. Thus, despite the importance of incorporating the evolutionary process into conservation efforts, we must also be careful to evaluate the likely form that the processes will take when the context (specifically, extent of isolation) has been highly modified.

Elevation and connectivity define genetic refugia for mountain sheep as climate warms - CLINTON W. EPPS; PER J. PALSBØLL; JOHN D. WEHAUSEN; GEORGE K. RODERICK; DALE R. MCCULLOUGH (Molecular Ecology, 2006)
Global warming is predicted to affect the evolutionary potential of natural populations. We assessed genetic diversity of 25 populations of desert bighorn sheep ( Ovis canadensis nelsoni ) in southeastern California, where temperatures have increased and precipitation has decreased during the 20th century. Populations in low‐elevation habitats had lower genetic diversity, presumably reflecting more fluctuations in population sizes and founder effects. Higher‐elevation habitats acted as reservoirs of genetic diversity. However, genetic diversity was also affected by population connectivity, which has been disrupted by human development. Restoring population connectivity may be necessary to buffer the effects of climate change on this desert‐adapted ungulate.

Are bottlenecks associated with colonization? Genetic diversity and diapause variation of native and introduced Rhagoletis completa populations - Yolanda H. Chen; Susan B. Opp; Stewart H. Berlocher; George K. Roderick (Oecologia, 2006)

Prevalence and penetrance variation of male‐killing Wolbachia across Indo‐Pacific populations of the butterfly Hypolimnas bolina - SYLVAIN CHARLAT; EMILY A. HORNETT; EMILY A. DYSON; PATRICK P. Y. HO; NGUYEN THI LOC; MENNO SCHILTHUIZEN; NEIL DAVIES; GEORGE K. RODERICK; GREGORY D. D. HURST (Molecular Ecology, 2005)
Male‐killing bacteria are generally thought to attain low to intermediate prevalence in natural populations, with only mild effects on the host population sex ratio. This view was recently challenged by reports of extremely high infection frequencies in three butterfly species, raising the prospect that male killers, by making males rare, might drive many features of host ecology and evolution. To assess this hypothesis, it is necessary to evaluate how often male killers actually produce a highly female‐biased population sex ratio in nature, which requires both high prevalence of infection and high penetrance of action. To this end, we surveyed South Pacific and Southeast Asian populations of Hypolimnas bolina , a butterfly in which extreme prevalence of male‐killing Wolbachia bacteria has recently been recorded. Our results indicate that highly female‐biased populations are common in Polynesia, with 6 out of 12 populations studied having in excess of 70% of females infected with a fully efficient male killer. However, heterogeneity is extreme in Polynesia, with the male‐killing Wolbachia absent from three populations. In contrast to the Polynesian situation, Wolbachia does not kill males in any of the three Southeast Asian populations studied, despite its very high prevalence there. We conclude that male killers are likely to have significant ongoing ecological and evolutionary impact in 6 of the 15 populations surveyed. The causes and consequences of the observed spatial variation are discussed with respect to host resistance evolution, host ecology and interference with additional symbionts.

Highways block gene flow and cause a rapid decline in genetic diversity of desert bighorn sheep - Clinton W. Epps; Per J. Palsbøll; John D. Wehausen; George K. Roderick; Rob R. Ramey; Dale R. McCullough (Ecology Letters, 2005)
The rapid expansion of road networks has reduced connectivity among populations of flora and fauna. The resulting isolation is assumed to increase population extinction rates, in part because of the loss of genetic diversity. However, there are few cases where loss of genetic diversity has been linked directly to roads or other barriers. We analysed the effects of such barriers on connectivity and genetic diversity of 27 populations of Ovis canadensis nelsoni (desert bighorn sheep). We used partial Mantel tests, multiple linear regression and coalescent simulations to infer changes in gene flow and diversity of nuclear and mitochondrial DNA markers. Our findings link a rapid reduction in genetic diversity (up to 15%) to as few as 40 years of anthropogenic isolation. Interstate highways, canals and developed areas, where present, have apparently eliminated gene flow. These results suggest that anthropogenic barriers constitute a severe threat to the persistence of naturally fragmented populations.

Population structure and colonization history of the olive fly, Bactrocera oleae (Diptera, Tephritidae) - FRANCESCO NARDI; ANTONIO CARAPELLI; ROMANO DALLAI; GEORGE K. RODERICK; FRANCESCO FRATI (Molecular Ecology, 2005)
The olive fly, Bactrocera oleae , is the major pest of olives in most commercial olive‐growing regions worldwide. The species is abundant in the Mediterranean basin and has been introduced recently into California and Mexico, creating problems for quarantine protection and international trade. Here, we use nuclear microsatellite markers and mitochondrial sequences to examine the history of olive fly range expansion and colonization. Sampled populations span the current distribution of the olive fly worldwide, including South and Central Africa, Pakistan, Mediterranean Europe and Middle East, California, and Mexico. The Pakistani populations appear to be genetically well differentiated from the remaining populations, though rooting the origins of the species is problematic. Genetic similarity and assignment tests cluster the remaining populations into two genetic groups — Africa and a group including the Mediterranean basin and the American region. That Africa, and not the Mediterranean, is the origin of flies infesting cultivated olive is supported by the significantly greater genetic diversity at microsatellite loci in Africa relative to the Mediterranean area. The results also indicate that the recent invasion of olive flies in the American region most likely originated from the Mediterranean area.

Influence of volcanic activity on the population genetic structure of Hawaiian Tetragnatha spiders: fragmentation, rapid population growth and the potential for accelerated evolution - Amy G. Vandergast; Rosemary G. Gillespie; George K. Roderick (Molecular Ecology, 2004)
Volcanic activity on the island of Hawaii results in a cyclical pattern of habitat destruction and fragmentation by lava, followed by habitat regeneration on newly formed substrates. While this pattern has been hypothesized to promote the diversification of Hawaiian lineages, there have been few attempts to link geological processes to measurable changes in population structure. We investigated the genetic structure of three species of Hawaiian spiders in forests fragmented by a 150‐year‐old lava flow on Mauna Loa Volcano, island of Hawaii: Tetragnatha quasimodo (forest and lava flow generalist), T. anuenue and T. brevignatha (forest specialists). To estimate fragmentation effects on population subdivision in each species, we examined variation in mitochondrial and nuclear genomes (DNA sequences and allozymes, respectively). Population subdivision was higher for forest specialists than for the generalist in fragments separated by lava. Patterns of mtDNA sequence evolution also revealed that forest specialists have undergone rapid expansion, while the generalist has experienced more gradual population growth. Results confirm that patterns of neutral genetic variation reflect patterns of volcanic activity in some Tetragnatha species. Our study further suggests that population subdivision and expansion can occur across small spatial and temporal scales, which may facilitate the rapid spread of new character states, leading to speciation as hypothesized by H. L. Carson 30 years ago.

Population structure of the pumpkin fruit fly Bactrocera depressa (Tephritidae) in Korea and Japan: Pliocene allopatry or recent invasion? - Jeomhee Mun; Andrew J. Bohonak; George K. Roderick (Molecular Ecology, 2003)
Because of their widespread agricultural impact and rapid range expansions, true fruit flies (Tephritidae) are the subject of quarantine and control efforts worldwide. Among these flies, the pumpkin fruit fly Bactrocera depressa, which infests squash and other cucurbitaceous plants in Korea, Japan and Taiwan, was recently isolated from produce shipments entering Japan and identified as a regulatory target. This species was described in 1933 from collections in Japan and discovered in 1974 in Korea, suggesting that it may have recently invaded mainland Asia. We analysed the genetic structure of Asian populations of B. depressa using sequence variation for mitochondrial gene cytochrome‐oxidase I and three nuclear loci: elongation factor 1α, tubulin β1 and tubulin β3, using frequency‐based approaches, nested clade analysis and assignment tests. Contrary to the hypothesis of recent invasion, high levels of genetic subdivision were found among five Korean and three Japanese populations. Nested clade analysis suggested a variety of processes operating over different time scales, including ancient isolation between Korea and Japan and more recent range expansions within each country. Contrary to a priori expectations, the results also suggested the recent introduction of a mitochondrial haplotype into Yokohama, Japan that is related closely to a widespread haplotype found throughout Korea. Assignment tests also supported these conclusions. The combination of a genealogical approach and probabilistic assignments of individuals to populations of origin was able to provide statistical support for the identification of cryptic introductions within an otherwise widespread indigenous species.

Isolation and Characterization of Nine Microsatellite Loci from the Hawaiian Grouper Epinephelus Quernus (Serranidae) for Population Genetic Analyses - Malia Ana J. Rivera; Glenn C. Graham; George K. Roderick (Marine Biotechnology, 2003)

Invasion Genetics of New World Medflies: Testing Alternative Colonization Scenarios - Andrew J. Bohonak; Neil Davies; Francis X. Villablanca; George K. Roderick (Biological Invasions, 2001)